Integrating Maqāṣid al-Sharī'ah into Islamic Religious Education Curriculum A Framework for Sustainable Character Development - Husna Husna; Khalid Abdullah Al Muzaini; Maryam Rashid Saleh Al Tamimi; Muneera Mohammed Al Dossary (PT Barkah Ilmi Fiddunya, 2025)
The implementation of Islamic Religious Education frequently emphasizes cognitive achievement while giving insufficient attention to the broader objectives of Islamic law (Maqāṣid al-Sharī'ah) as the foundation of character formation. This study aims to develop an integrative curriculum framework that incorporates Maqāṣid al-Sharī'ah principles into Islamic Religious Education to foster sustainable character development. A qualitative research design employing document analysis and expert validation was utilized. Data were collected from curriculum documents, educational policies, classical Islamic literature, and interviews with curriculum experts and Islamic education scholars. The results reveal that integrating the five essential dimensions of Maqāṣid al-Sharī'ah protection of religion, life, intellect, lineage, and wealth significantly enriches curriculum content, instructional strategies, and authentic assessment practices. The framework also promotes students' ethical decision-making, social responsibility, environmental awareness, and lifelong learning competencies. Furthermore, curriculum integration encourages interdisciplinary learning aligned with Sustainable Development Goals (SDGs). The novelty of this research lies in constructing a comprehensive Maqāṣid-based curriculum model specifically designed for contemporary Islamic Religious Education, bridging classical Islamic educational philosophy with twenty-first-century educational demands